Positive electrode material and preparation method thereof, positive electrode plate, positive electrode slurry and preparation method thereof, battery and electric device

By providing an organic polymer cladding layer on the surface of the positive electrode active material, the problem of metal ions precipitation of secondary batteries in the aqueous positive electrode slurry is solved, and the cycle performance and service life of the battery are improved.

CN119852333APending Publication Date: 2025-04-18CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311352010.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-18
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The oily positive electrode slurry used in the coating preparation process of existing secondary batteries has problems such as human health, environmental pollution and difficulty in recycling. At the same time, in the aqueous positive electrode slurry, the positive electrode active material is prone to precipitation of metal ions, resulting in a degradation of the cell circulation performance.

Method used

A cladding layer composed of organic polymers is provided on the surface of the positive electrode active material, especially a hydrophobic organic polymer cladding layer, to prevent the contact between water and the positive electrode active material and reduce the problem of metal ions precipitation.

Benefits of technology

Through the barrier of the cladding layer, the cycling performance of the battery is improved, the metal ion loss of the positive electrode active material is reduced, the moisture content of the battery is reduced, and the service life of the battery is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852333A_ABST
    Figure CN119852333A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a positive electrode material and a preparation method thereof, a positive electrode plate, positive electrode slurry and a preparation method thereof, a battery and an electric device. The positive electrode material comprises a positive electrode active material and a coating layer arranged on the surface of the positive electrode active material, the coating layer comprises an organic polymer, and preferably, the coating layer comprises a hydrophobic organic polymer. According to the invention, the coating layer composed of the organic polymer is arranged on the surface of the positive electrode active material, so that the contact between water and the positive electrode active material is blocked through the blocking of the coating layer in the preparation process of the aqueous positive electrode slurry, thereby alleviating the problem of metal ion precipitation in the positive electrode active material, and improving the cycle performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a positive electrode material and a preparation method thereof, a positive electrode sheet, a positive electrode slurry and a preparation method thereof, a battery and an electrical device. Background Art

[0002] Secondary batteries have been widely used in various consumer electronic products and electric vehicles due to their advantages such as high energy density, high output voltage, good safety, no pollution and no memory effect.

[0003] Oily positive electrode slurry is usually used in the preparation process of secondary battery coating. However, oily solvents have problems such as harming human health, being difficult to recycle, and causing environmental pollution during the electrode preparation process, which limits the manufacture and application of secondary batteries around the world. Summary of the invention

[0004] The main purpose of the present invention is to provide a positive electrode material to improve the performance of the battery.

[0005] To achieve the above object, the present invention provides a positive electrode material, comprising a positive electrode active material and a coating layer disposed on the surface of the positive electrode active material, wherein the coating layer comprises an organic polymer, and preferably, the coating layer comprises a hydrophobic organic polymer.

[0006] In order to provide aqueous cathode slurry, aqueous cathode systems using deionized water as slurry solvent have attracted much attention. However, cathode active materials are prone to precipitate metal ions in aqueous solvents, resulting in decreased battery cell cycle performance.

[0007] In order to solve the above problems, the present application sets a coating layer composed of an organic polymer on the surface of the positive electrode active material, so that in the process of preparing the aqueous positive electrode slurry, the coating layer blocks the contact between water and the positive electrode active material, thereby reducing the problem of metal ion precipitation in the positive electrode active material, thereby improving the cycle performance of the battery. Of course, the positive electrode active material in the present application can also be applied to non-aqueous positive electrode slurry.

[0008] It can be understood that the coating layer comprising a hydrophobic organic polymer means that it is difficult for water outside the coating layer to pass through the coating layer to reach the positive electrode active material.

[0009] Optionally, the coating layer comprises an organic polymer, preferably, the coating layer comprises a hydrophobic organic polymer.

[0010] Organic polymers have good water stability, and the coating layer including organic polymers can effectively block the contact between water and the positive electrode active material. In addition, organic polymers will not be decomposed during the battery cycle and will not produce substances harmful to the battery.

[0011] The organic polymer includes a porous structure that can accommodate the electrolyte and improve the liquid retention capacity of the positive electrode material in the positive electrode coating. At the same time, the porous structure can also serve as a channel for ion transmission.

[0012] In order to improve the water-isolating effect of the coating layer, the coating layer includes a hydrophobic organic polymer. The hydrophobic property of the organic polymer is utilized to better block water outside the coating layer. In addition, the hydrophobic organic polymer also reduces the risk of water entering the positive electrode active material through the pores of the organic polymer.

[0013] Optionally, the hydrophobic organic polymer includes at least one of polycarbonate, polyolefin, polyamide and polyacrylonitrile.

[0014] The hydrophobic organic polymer includes, but is not limited to, at least one of polycarbonate, polyolefin, polyamide, and polyacrylonitrile.

[0015] It is understandable that these hydrophobic organic polymers can form a coating layer by polymerizing monomers on the surface of the positive electrode active material. For example, when the hydrophobic polymer includes polycarbonate, the positive electrode active material (for example, lithium iron phosphate) is mixed with a carbonate solvent containing a catalyst, and the carbonate ring opening is catalyzed by the catalyst to form a polycarbonate coating layer on the surface of the positive electrode active material, thereby reducing the dissolution of lithium ions and iron ions of lithium iron phosphate particles, and hindering the process of combining with water on the surface of the particles to form bound water. At the same time, the ester substance coated on the surface of the lithium iron phosphate particles can have a good bonding force with the ester group of the water-based binder, which can improve the bonding force of the pole piece.

[0016] In addition, lithium iron phosphate easily forms bound water with water, which makes the water content of the manufactured pole piece high and difficult to remove, thus reducing the battery life. Through the scheme of the present application, the problem of lithium iron phosphate forming bound water with water can be alleviated, the water content of the pole piece can be reduced, and the battery life can be increased.

[0017] Optionally, the coating layer includes a solid electrolyte and / or a conductive agent;

[0018] The mass of the solid electrolyte accounts for 0.01% to 2% of the total mass of the coating layer, preferably 0.5% to 1.5%, and the solid electrolyte includes at least one of P2O5, B2O3, SiO2, Li2O, Li2S, SiS2, LiPON, LiSiPON, and LiSON;

[0019] The mass of the conductive agent accounts for 0.01% to 2% of the total mass of the coating layer, preferably 0.5% to 1.5%, and the conductive agent includes at least one of SP and CNT.

[0020] Including a solid electrolyte in the coating layer can help lithium ion migration, and including a conductive agent in the coating layer can improve electronic conduction.

[0021] Optionally, the mass of the coating layer accounts for 0.01% to 2% of the total mass of the positive electrode material, preferably 0.1% to 1.5%.

[0022] It is understood that when the mass of the coating layer is within the above range, water can be effectively blocked from passing through the coating layer to the positive electrode active material, and the problem of reduced mass energy density of the positive electrode material can also be alleviated. In the above preferred range, the prepared coating layer is more stable.

[0023] Optionally, the coating layer has a thickness ranging from 1 nm to 200 nm, preferably, from 10 nm to 50 nm.

[0024] It can be understood that the thickness of the coating layer within the above range can improve the water-isolating ability of the coating layer, while also improving the passage performance of lithium ions through the coating layer. In addition, the thickness of the coating layer within the above range can also alleviate the problem of reduced volume energy density of the positive electrode material.

[0025] Optionally, the coating layer has a coverage rate of 80% to 100% on the surface of the positive electrode active material.

[0026] That is, the coating layer can be coated on the surface of the positive electrode active material in the form of full coating or non-full coating. It can be understood that full coating means that the coating layer is continuously arranged on the surface of the positive electrode active material so that the positive electrode active material is not exposed. In this way, during the preparation of the positive electrode slurry, the positive electrode active material will not be exposed from the coating layer and contact with water, thereby improving the water-isolating effect of the coating layer.

[0027] Optionally, the surface of the positive electrode active material includes adsorption groups, and the adsorption groups include at least one of hydroxyl groups, amino groups, and carboxyl groups.

[0028] Some positive electrode active materials have some adsorption groups such as hydroxyl and carboxyl on their surfaces. These adsorption groups on the surface of the positive electrode active materials help the constituent monomers of the organic polymer to be effectively adsorbed on the surface of the positive electrode active material, making it convenient for the constituent monomers of the organic polymer to polymerize on the surface of the positive electrode active material to form a coating layer, which helps the coating layer to be effectively coated on the surface of the positive electrode active material.

[0029] Of course, in addition to the adsorption groups on the surface of the positive electrode active material, adsorption groups can also be modified on the surface of the positive electrode active material by modification.

[0030] It is understood that the adsorption group includes but is not limited to at least one of a hydroxyl group, an amino group, and a carboxyl group. A suitable adsorption group can be selected according to the properties of the constituent monomers of the organic polymer. For example, when the constituent monomers of the organic polymer include hydroxyl groups, hydroxyl groups, amino groups, carboxyl groups, etc. can be modified on the surface of the positive electrode active material so that the constituent monomers of the organic polymer are adsorbed to the surface of the positive electrode active material through hydrogen bonding or van der Waals forces.

[0031] It can also be understood that the positive electrode active material can be treated with a modifying agent to modify the surface of the positive electrode active material with suitable adsorption groups. For example, the modifying agent includes γ-aminopropyltrimethoxysilane, acetyl well, and maleic anhydride. The positive electrode active material is mixed with the modifying agent to obtain a modified positive electrode active material so that the surface of the positive electrode active material includes adsorption groups.

[0032] Optionally, the positive electrode active material includes at least one of a layered lithium transition metal oxide, an olivine phase lithium-containing phosphate, and a spinel phase lithium-containing manganese-based oxide.

[0033] Optionally, the positive electrode active material includes at least one of the compounds represented by formula (1), formula (2) and formula (3),

[0034] Li a1 Ni x1 Co y1 M1 z1 R b1 O c1 Formula (1)

[0035] In the formula (1), 0.6≤a1≤1.2, 0.3≤x1≤1, 0≤y1≤0.4, 0<z1≤0.2, 0<b1≤0.2, 1.8≤c1≤2.2, x1+y1+z1+b1=1, M1 is selected from one or two of Mn and Al, and R includes one or more of Na, Sb, K, Ca, Zr, Sr, Al, B, Ba, Nb, W, Mo, Co, Ti, and Mg;

[0036] Li x2 A y2 Me a2 M2 b2 P 1-c2 X c2 Y z2 Formula (2)

[0037] In formula (2), 0.5 ≤ x2 ≤ 1.3, 0 ≤ y2 ≤ 1.3, and 0.9 ≤ x2 + y2 ≤ 1.3; 0.9 ≤ a2 ≤ 1.5, 0 ≤ b2 ≤ 0.5, and 0.9 ≤ a2 + b2 ≤ 1.5; 0 ≤ c2 ≤ 0.5; 3 ≤ z2 ≤ 5; A includes one or more of Na, K, and Mg; Me includes one or more of Mn, Fe, Co, and Ni; M2 includes one or more of B, Mg, Al, Si, P, S, Ca, Sc, Ti, V, Cr, Cu, Zn, Sr, Y, Zr, Nb, Mo, Cd, Sn, Sb, Te, Ba, Ta, W, Yb, La, and Ce; X includes one or more of S, Si, Cl, B, C, and N; Y includes one or more of O and F.

[0038] Li 1+z3 Mn c3 Z 2-c3 O 4-d B d Formula (3)

[0039] In formula (3), -0.5 ≤ z3 ≤ 0.2, 0 < c3 ≤ 2, 0 ≤ d < 1, Z includes one or more of Ni, Fe, Cr, Ti, Zn, V, Al, Mg, Zr, and Ce, and B includes one or more of S, N, F, Cl, Br, and I.

[0040] It can be understood that the positive electrode active material includes, but is not limited to, at least one of layered lithium transition metal oxides, olivine phase lithium-containing phosphates, and spinel phase lithium-containing manganese-based oxides. Further, the positive electrode active material includes, but is not limited to, at least one of the compounds of formula (1), formula (2), and formula (3). For example, Li a1 Ni x1 Co y1 M1 z1 R b1 O c1 Formula (1), in formula (1), 0.6 ≤ a1 ≤ 1.2, 0.3 ≤ x1 ≤ 1, 0 ≤ y1 ≤ 0.4, 0 < z1 ≤ 0.2, 0 < b1 ≤ 0.2, 1.8 ≤ c1 ≤ 2.2, x1 + y1 + z1 + b1 = 1, M1 is selected from one or two of Mn and Al, and R includes one or more of Na, Sb, K, Ca, Zr, Sr, Al, B, Ba, Nb, W, Mo, Co, Ti, and Mg; Li x2 A y2 Me a2 M2 b2 P 1-c2 X c2 Y z2Formula (2), in Formula (2), 0.5 ≤ x2 ≤ 1.3, 0 ≤ y2 ≤ 1.3, and 0.9 ≤ x2 + y2 ≤ 1.3; 0.9 ≤ a2 ≤ 1.5, 0 ≤ b2 ≤ 0.5, and 0.9 ≤ a2 + b2 ≤ 1.5; 0 ≤ c2 ≤ 0.5; 3 ≤ z2 ≤ 5; A includes one or more of Na, K, and Mg; Me includes one or more of Mn, Fe, Co, and Ni; M2 includes one or more of B, Mg, Al, Si, P, S, Ca, Sc, Ti, V, Cr, Cu, Zn, Sr, Y, Zr, Nb, Mo, Cd, Sn, Sb, Te, Ba, Ta, W, Yb, La, and Ce; X includes one or more of S, Si, Cl, B, C, and N; Y includes one or more of O and F; Li 1+z3 Mn c3 Z 2-c3 O 4-d B d Formula (3), in Formula (3), -0.5 ≤ z3 ≤ 0.2, 0 < c3 ≤ 2, 0 ≤ d < 1, Z includes one or more of Ni, Fe, Cr, Ti, Zn, V, Al, Mg, Zr, and Ce, and B includes one or more of S, N, F, Cl, Br, and I.

[0041] Optionally, the present application further provides a method for preparing a cathode material, including:

[0042] Providing a cathode active material;

[0043] Mixing the cathode active material with a constituent monomer of an organic polymer to obtain a first mixed solution;

[0044] Mixing an initiator, a catalyst, and a solvent to obtain a second mixed solution;

[0045] Mixing the first mixed solution with the second mixed solution and heating to obtain the cathode material, the cathode material including the cathode active material and a coating layer provided on the surface of the cathode active material, the coating layer including the organic polymer, and preferably, the coating layer includes a hydrophobic organic polymer.

[0046] That is, the coating layer of the organic polymer is formed by polymerizing monomers on the surface of the positive electrode active material. In the step of preparing the positive electrode material, a positive electrode active material is provided, and the positive electrode active material is mixed with the constituent monomers of the organic polymer to obtain a first mixed liquid, so that the constituent monomers of the organic polymer are arranged on the surface of the positive electrode active material to facilitate the polymerization reaction of the constituent monomers of the organic polymer on the surface of the positive electrode active material, thereby forming a coating layer, and an initiator, a catalyst and a solvent are mixed to obtain a second mixed liquid, that is, an initiator and a catalyst for the polymerization reaction of the constituent monomers of the organic polymer are prepared, the first mixed liquid is mixed with the second mixed liquid, so that the constituent monomers of the organic polymer are in contact with the initiator and the catalyst, and the positive electrode material is heated to obtain the positive electrode material, which includes the positive electrode active material and a hydrophobic coating layer arranged on the surface of the positive electrode active material.

[0047] Optionally, the step of mixing the positive electrode active material with a constituent monomer of an organic polymer to obtain a first mixed solution includes:

[0048] The positive electrode active material is mixed with a constituent monomer of an organic polymer, a solid electrolyte and / or a conductive agent to obtain a first mixed solution.

[0049] In order to include a solid electrolyte and / or a conductive agent in the coating layer, the solid electrolyte and / or the conductive agent are added during the process of mixing the positive electrode active material with the constituent monomers of the organic polymer, so that the constituent monomers of the organic polymer can mix the solid electrolyte and / or the conductive agent into the coating layer during the polymerization process.

[0050] Optionally, the mass ratio of the positive electrode active material, the constituent monomer of the organic polymer, the initiator, and the catalyst is (88%-99.9%): (0.1%-4%): (0%-4%): (0%-4%), preferably, (95.5%-98.5%): (0.5%-1.5%): (0.5%-1.5%): (0.5% to 1.5%);

[0051] And / or, the initiator includes at least one of an organic peroxide, an inorganic peroxide, an azo compound, benzyl alcohol, and potassium permanganate; the organic peroxide includes at least one of benzoyl peroxide and methyl ethyl ketone peroxide; the inorganic peroxide includes at least one of potassium persulfate and ammonium persulfate; and the azo compound includes azobisisobutyronitrile;

[0052] And / or, the catalyst comprises at least one of 1,8-diazabicycloundec-7-ene, tetrabutylammonium bromide, and p-toluenesulfonic acid;

[0053] And / or, the solvent includes at least one of dichloromethane, sodium bisphenolate aqueous solution, and toluene;

[0054] And / or, the constituent monomers of the organic polymer include at least one of alkylene carbonates, olefins, and amides.

[0055] In the step of preparing the positive electrode material, the mass ratio of the positive electrode active material, the constituent monomers of the organic polymer, the initiator, and the catalyst is (88%-99.9%): (0.1%-4%): (0%-4%): (0%-4%), preferably, (95.5%-98.5%): (0.5%-1.5%): (0.5%-1.5%): (0.5%-1.5%). The mass ratio of each raw material is within the above range, which can effectively prepare the positive electrode material.

[0056] It is understood that an initiator refers to a substance that can initiate a polymerization reaction of a monomer. For example, a free radical initiator refers to a compound that is easily decomposed into free radicals (i.e., primary free radicals) by heat, and can be used to initiate free radical polymerization and copolymerization reactions of olefinic and diene monomers. Initiators include, but are not limited to, at least one of organic peroxides (such as benzoyl peroxide, methyl ethyl ketone peroxide, etc.), inorganic peroxides (such as potassium persulfate, ammonium persulfate, etc.), azo compounds (such as azobisisobutyronitrile, etc.), benzyl alcohol, and potassium permanganate. Those skilled in the art can select a suitable initiator according to the type of monomers constituting the organic polymer.

[0057] Catalysts are substances that can change the chemical reaction rate of reactants in chemical reactions (either increase or decrease) without changing the chemical equilibrium, and whose quality and chemical properties do not change before and after the chemical reaction. Catalysts include but are not limited to at least one of 1,8-diazabicycloundec-7-ene, tetrabutylammonium bromide, and p-toluenesulfonic acid. Those skilled in the art can select a suitable catalyst according to the needs of the monomer polymerization reaction.

[0058] The solvent in the present application includes but is not limited to at least one of dichloromethane, sodium bisphenolate aqueous solution, and toluene.

[0059] The constituent monomers of the organic polymer in the present application include but are not limited to at least one of olefin carbonates, olefin acids, olefins, and amides. Those skilled in the art can select appropriate monomers to polymerize the coating layer according to the material of the coating layer.

[0060] Optionally, the step of mixing the positive electrode active material with a monomer constituting an organic polymer to obtain a first mixed solution, mixing an initiator, a catalyst and a solvent to obtain a second mixed solution, mixing the first mixed solution with the second mixed solution, and heating to obtain a positive electrode material includes:

[0061] The positive electrode active material is mixed with the constituent monomer ethylene carbonate of the organic polymer to obtain a first mixed solution, benzyl alcohol initiator and 1,8-diazabicycloundec-7-ene catalyst are added into dichloromethane and dissolved to obtain a second mixed solution, the first mixed solution and the second mixed solution are mixed, heated to 50° C. to 60° C., and reacted for 6 h to 8 h to obtain the positive electrode material.

[0062] Optionally, the present application further provides a positive electrode plate, the positive electrode plate comprising a current collector and a positive electrode coating provided on at least one side of the current collector, the positive electrode coating comprising the positive electrode material as described above;

[0063] Alternatively, the positive electrode plate includes a current collector and a positive electrode coating disposed on at least one side of the current collector, and the positive electrode coating includes a positive electrode material prepared by the method for preparing the positive electrode material.

[0064] Optionally, the cathode coating includes a dispersant;

[0065] And / or, the positive electrode coating comprises a binder, and the binder comprises an aqueous binder;

[0066] And / or, the positive electrode coating includes a conductive agent.

[0067] In order to improve the dispersibility of the positive electrode material and make it evenly distributed in the positive electrode coating, the positive electrode coating includes a dispersant. For example, the dispersant includes but is not limited to polyethyleneimine, polyethylene glycol octylphenyl ether, and the like.

[0068] The positive electrode coating includes a binder, which refers to a material with bonding properties, which is used to bond different substances together. The binder is used to effectively bond the components in the positive electrode coating together. The binder includes an aqueous binder. It can be understood that, in theory, the binder can be oily or aqueous. In an aqueous slurry system, an aqueous binder is used, and in an oily slurry system, an oily binder is used.

[0069] The positive electrode coating includes a conductive agent. The conductive agent is to ensure that the electrode has good charge and discharge performance. A certain amount of conductive material is usually added when the electrode is made. It plays the role of collecting microcurrents between active materials and between active materials and current collectors, so as to reduce the contact resistance of the electrode and accelerate the movement rate of electrons. At the same time, it can also effectively increase the migration rate of lithium ions in the electrode material, thereby improving the charge and discharge efficiency of the electrode.

[0070] Optionally, the positive electrode coating includes a dispersant, and the mass of the dispersant accounts for 0.01% to 0.7% of the total mass of the positive electrode coating, preferably 0.1% to 0.5%;

[0071] And / or, the positive electrode coating comprises an aqueous binder, and the mass of the aqueous binder accounts for 0.1% to 5% of the total mass of the positive electrode coating, preferably, 2% to 4%;

[0072] And / or, the positive electrode coating includes a conductive agent, and the mass of the conductive agent accounts for 0.1% to 5% of the total mass of the positive electrode coating, preferably, 0.5% to 3%.

[0073] It is understood that the mass of the dispersant accounts for 0.01% to 0.7% of the total mass of the positive electrode coating, preferably 0.1% to 0.5%. The dispersant satisfies the above range and can effectively disperse the components in the positive electrode coating.

[0074] It can be understood that the mass of the aqueous binder accounts for 0.1% to 5% of the total mass of the positive electrode coating, preferably 2% to 4%. The aqueous binder meets the above range so that the components in the positive electrode coating are effectively bonded together.

[0075] It can be understood that the mass of the conductive agent accounts for 0.1% to 5% of the total mass of the positive electrode coating, preferably 0.5% to 3%. The conductive agent meets the above range to improve the charge and discharge efficiency of the battery.

[0076] Optionally, the positive electrode coating includes a dispersant, and the dispersant includes at least one of a cationic dispersant and an amphoteric dispersant;

[0077] And / or, the positive electrode coating comprises an aqueous binder, and the aqueous binder comprises at least one of methyl cellulose and its salts, xanthan gum and its salts, chitosan and its salts, alginic acid and its salts, polyacrylamide, acrylonitrile-acrylic acid copolymer and its derivatives, acrylonitrile-acrylate copolymer, and acrylonitrile-acrylic acid-acrylate copolymer;

[0078] And / or, the positive electrode coating includes a conductive agent, and the conductive agent includes at least one of carbon black, graphite, graphene, and carbon nanotubes.

[0079] It is understood that the dispersant includes but is not limited to at least one of a cationic dispersant and an amphoteric dispersant.

[0080] The aqueous binder includes, but is not limited to, at least one of methylcellulose and its salts, xanthan gum and its salts, chitosan and its salts, alginic acid and its salts, polyacrylamide, acrylonitrile-acrylic acid copolymer and its derivatives, acrylonitrile-acrylate copolymer, and acrylonitrile-acrylic acid-acrylate copolymer.

[0081] The conductive agent includes but is not limited to at least one of carbon black, graphite, graphene, and carbon nanotubes.

[0082] Optionally, the positive electrode coating includes at least one of a cationic dispersant and an amphoteric dispersant, the cationic dispersant includes at least one of an amine salt, a quaternary ammonium salt, and a pyridinium salt, and the amphoteric dispersant includes at least one of a phosphate salt and polyacrylamide;

[0083] And / or, the positive electrode coating comprises a binder, the binder comprises acrylonitrile-acrylic acid-acrylate copolymer, preferably, the acrylonitrile-acrylic acid-acrylate copolymer has a number average molecular weight of 300,000 to 2,000,000.

[0084] The cationic dispersant includes but is not limited to at least one of amine salts, quaternary ammonium salts, and pyridinium salts, and the amphoteric dispersant includes but is not limited to at least one of phosphate salts and polyacrylamide.

[0085] It can be understood that cationic dispersants: interact with negatively charged surfaces and disperse particles well in water through electrostatic adsorption; amphoteric dispersants: form a bimolecular structure on the surface of the material. Amphoteric dispersants have a strong affinity for water, which increases the degree of wetting of solid particles by water. The solid particles move away from each other due to electrostatic repulsion to achieve a good dispersion effect.

[0086] Dispersants can be divided into cationic dispersants, amphoteric dispersants, anionic dispersants, nonionic dispersants, etc. according to the different electrical properties of the ions they generate in water. Cationic dispersants refer to compounds that generate positive charges in water, while amphoteric dispersants refer to compounds that generate positive and negative charges in water.

[0087] Number average molecular weight is a type of average molecular weight of polymers. The number average molecular weight is tested as follows:

[0088] The solvent is water, and the analytical chromatographic column is a water column; an ultra-high performance polymer chromatograph is used: ACQUITY APC; and a detector is an ACQUITY differential refractometer.

[0089] The test steps are as follows: (1) Preheating: install the chromatographic column and pipelines, turn on the console in turn, test the power supply, etc., and open the test software Empower; (2) Parameter setting, injection volume: 0μL to 50μL (depending on the sample concentration); pump flow rate: 0.2mL / min; mobile phase: 30mol / LLiBr in NMP solution; seal cleaning liquid: isopropanol; pre-column: PLgel10umMiniMIX-BGuard (size: 50mm×4.6mm×2); analytical phase: PLgel10umMiniMIX-B (size: 250mm×4.6mm); standard: polystyrene sleeve; running time: 30min; detector: ACQUITY differential refractive index (RI) detector; column oven temperature: 90℃; detector temperature: 55℃. (3) Sample testing: a. Standard sample and test sample preparation: Weigh 0.002g to 0.004g of standard sample / test sample respectively and add 2mL of mobile phase liquid to prepare a 0.1% to 0.5% mixed standard, and store in the refrigerator for >8h; b. Standard solution / sample testing: Edit the sample group to be tested, select the established sample group method, and after the baseline is stable, click the run queue to start testing the sample; (4) Data processing: Based on the relationship between retention time and molecular weight, use the chemical workstation to establish a calibration curve, integrate and quantify the sample spectrum, and the chemical workstation automatically generates the molecular weight and molecular weight distribution results.

[0090] The acrylonitrile-acrylic acid-acrylate copolymer has good adhesion and flexibility, and using it as a binder can improve the adhesion between the positive electrode coating and the current collector. The number average molecular weight of the acrylonitrile-acrylic acid-acrylate copolymer is within the above range, so that the acrylonitrile-acrylic acid-acrylate copolymer has good adhesion and suitable viscosity.

[0091] Optionally, the present application further provides a positive electrode slurry, the positive electrode slurry comprising the positive electrode material as described;

[0092] Alternatively, the positive electrode slurry includes the positive electrode material prepared by the positive electrode material preparation method as described above.

[0093] Optionally, the positive electrode slurry includes a dispersant, the mass of the dispersant accounts for 0.01% to 0.7% of the total mass of the solid matter in the positive electrode slurry, preferably 0.1% to 0.5%, and the dispersant includes at least one of a cationic dispersant and an amphoteric dispersant;

[0094] And / or, the positive electrode slurry includes an aqueous binder, the mass of the aqueous binder accounts for 0.1% to 5% of the total mass of solid matter in the positive electrode slurry, preferably 2% to 4%, and the aqueous binder includes at least one of methyl cellulose and its salts, xanthan gum and its salts, chitosan and its salts, alginic acid and its salts, polyacrylamide, acrylonitrile-acrylic acid copolymer and its derivatives, acrylonitrile-acrylate copolymer, and acrylonitrile-acrylic acid-acrylate copolymer;

[0095] And / or, the positive electrode slurry includes a conductive agent, the mass of the conductive agent accounts for 0.1% to 5% of the total mass of solid matter in the positive electrode slurry, preferably 0.5% to 3%, and the conductive agent includes at least one of carbon black, graphite, graphene, and carbon nanotubes.

[0096] Optionally, the positive electrode slurry includes a solvent, and the solvent includes water;

[0097] And / or, the solid content of the positive electrode slurry is 40% to 90%, preferably, 50% to 70%;

[0098] And / or, the viscosity of the positive electrode slurry is 100 cp to 10000 cp, preferably, 3000 cp to 7000 cp.

[0099] The positive electrode slurry of the present application can be an aqueous positive electrode slurry, that is, the solvent includes water. In an aqueous environment, the positive electrode material of the present application has good stability. A coating layer is arranged on the surface of the positive electrode active material, so that during the preparation process of the aqueous positive electrode slurry, the coating layer blocks the contact between water and the positive electrode active material, thereby reducing the problem of metal ion precipitation in the positive electrode active material, thereby improving the cycle performance of the battery.

[0100] The solid content of the positive electrode slurry is within the above range, which can improve the processing performance of the slurry and reduce the problem of cracking of the electrode piece. The viscosity of the positive electrode slurry is within the above range, which facilitates the processing of the slurry.

[0101] Optionally, the present application also provides a method for preparing the positive electrode slurry as described above, comprising:

[0102] Mixing a positive electrode material and a conductive agent to form a mixture;

[0103] The mixture, the dispersant, the aqueous binder and the solvent water are mixed to obtain a positive electrode slurry.

[0104] The present application also provides a battery, which includes the positive electrode plate as described above.

[0105] The present application also provides an electrical device, which includes the battery as described above.

[0106] The present application sets a coating layer on the surface of the positive electrode active material, so that during the preparation of the aqueous positive electrode slurry, the coating layer blocks the contact between water and the positive electrode active material, thereby alleviating the problem of metal ion precipitation in the positive electrode active material, thereby improving the cycle performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0107] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.

[0108] Figure 1 A schematic diagram of the structure of a positive electrode material according to an embodiment of the present application;

[0109] Figure 2 is a schematic diagram of a battery cell according to an embodiment of the present application;

[0110] Figure 3 yes Figure 2 An exploded view of a battery cell according to an embodiment of the present application is shown;

[0111] Figure 4 is a schematic diagram of a battery module according to an embodiment of the present application;

[0112] Figure 5 is a schematic diagram of a battery pack according to an embodiment of the present application;

[0113] Figure 6 yes Figure 5 An exploded view of a battery pack according to an embodiment of the present application is shown;

[0114] Figure 7 It is a schematic diagram of an electrical device using a battery cell according to an embodiment of the present application as a power source.

[0115] Description of Figure Numbers:

[0116] Label name Label name 1 Battery Pack 5 Battery Cell 2 Upper box 51 case 3 Lower box 52 Electrode assembly 4 Battery Module 53 Cover 100 Cathode Materials 10 Positive electrode active material 20 Coating

[0117] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0118] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0119] Hereinafter, the positive electrode material and its preparation method, positive electrode sheet, positive electrode slurry and its preparation method, battery and electric device of the present application are specifically disclosed in detail with appropriate reference to the drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0120] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0121] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0122] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0123] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0124] Secondary batteries have been widely used in various consumer electronic products and electric vehicles due to their advantages such as high energy density, high output voltage, good safety, no pollution and no memory effect.

[0125] Oily positive electrode slurry is usually used in the preparation process of secondary battery coating. However, oily solvents have problems such as harming human health, being difficult to recycle, and causing environmental pollution during the electrode preparation process, which limits the manufacture and application of secondary batteries around the world.

[0126] In order to provide aqueous cathode slurry, aqueous cathode systems using deionized water as slurry solvent have attracted much attention. However, cathode active materials are prone to precipitate metal ions in aqueous solvents, resulting in decreased battery cell cycle performance.

[0127] In order to solve the above problems, the present application sets a coating layer on the surface of the positive electrode active material, and the coating layer includes an organic polymer. Preferably, the coating layer includes a hydrophobic organic polymer, so that in the process of preparing the aqueous positive electrode slurry, the coating layer blocks the contact between water and the positive electrode active material, thereby reducing the problem of metal ion precipitation in the positive electrode active material, thereby improving the cycle performance of the battery. Of course, the positive electrode active material in the present application can also be applied to non-aqueous positive electrode slurry.

[0128] like Figure 1 , which is a schematic structural diagram of a positive electrode material 100 , a hydrophobic coating layer 20 is disposed on the surface of the positive electrode active material 10 .

[0129] Test steps for coating layer: Use focused ion beam to cut the cathode material with coating layer into thin slices, put the cut main material particles in a vial and add ethanol to about 2 / 3 of the vial, ultrasonically disperse for 15 minutes, and let it stand for about 5 minutes. Use a pipette to transfer 1-2 drops of the upper clear liquid to the copper mesh and bake it with an infrared lamp; the prepared sample is observed under a field emission transmission electron microscope (Thermo Scientific-Talos F200S G2), and the coating thickness is measured by a ruler.

[0130] In one embodiment, the coating layer comprises an organic polymer, preferably, the coating layer comprises a hydrophobic organic polymer.

[0131] Organic polymers have good water stability, and the coating layer including organic polymers can effectively block the contact between water and the positive electrode active material. In addition, organic polymers will not be decomposed during the battery cycle and will not produce substances harmful to the battery.

[0132] The organic polymer includes a porous structure that can accommodate the electrolyte and improve the liquid retention capacity of the positive electrode material in the positive electrode coating. At the same time, the porous structure can also serve as a channel for ion transmission.

[0133] In order to improve the water-isolating effect of the coating layer, the coating layer includes a hydrophobic organic polymer. The hydrophobic property of the organic polymer is utilized to better block water outside the coating layer. In addition, the hydrophobic organic polymer also reduces the risk of water entering the positive electrode active material through the pores of the organic polymer.

[0134] In one embodiment, the hydrophobic organic polymer includes at least one of polycarbonate, polyolefin, polyamide, and polyacrylonitrile.

[0135] The hydrophobic organic polymer includes, but is not limited to, at least one of polycarbonate, polyolefin, polyamide, and polyacrylonitrile.

[0136] It is understandable that these hydrophobic organic polymers can form a coating layer by polymerizing monomers on the surface of the positive electrode active material. For example, when the hydrophobic polymer includes polycarbonate, the positive electrode active material (for example, lithium iron phosphate) is mixed with a carbonate solvent containing a catalyst, and the carbonate ring opening is catalyzed by the catalyst to form a polycarbonate coating layer on the surface of the positive electrode active material, thereby reducing the dissolution of lithium ions and iron ions of lithium iron phosphate particles, and hindering the process of combining with water on the surface of the particles to form bound water. At the same time, the ester substance coated on the surface of the lithium iron phosphate particles can have a good bonding force with the ester group of the water-based binder, which can improve the bonding force of the pole piece.

[0137] In one embodiment, the mass of the coating layer accounts for 0.01% to 2% of the total mass of the positive electrode material, preferably, 0.1% to 1.5%.

[0138] It is understood that when the mass of the coating layer is within the above range, water can be effectively blocked from passing through the coating layer to the positive electrode active material, and the problem of reduced mass energy density of the positive electrode material can also be alleviated. In the above preferred range, the prepared coating layer is more stable.

[0139] In the above 0.01% to 2%, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 0.01%, 0.02%, 0.05%, 0.08%, 0.1%, 0.3%, 0.5%, 08%, 1%, 1.2%, 1.4%, 1.5%, 1.7%, 1.8%, 2%, etc., as well as the range values ​​between any two of the above point values.

[0140] In the above 0.1% to 1.5%, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 0.1%, 0.3%, 0.5%, 08%, 1%, 1.2%, 1.4%, 1.5%, etc., as well as the range values ​​between any two of the above point values.

[0141] In one embodiment, the thickness of the coating layer ranges from 1 nm to 200 nm, preferably, from 10 nm to 50 nm.

[0142] It can be understood that the thickness of the coating layer within the above range can improve the water-isolating ability of the coating layer, while also improving the passage performance of lithium ions through the coating layer. In addition, the thickness of the coating layer within the above range can also alleviate the problem of reduced volume energy density of the positive electrode material.

[0143] In the above 10nm to 50nm, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 20nm, 40nm, etc., and the range values ​​between any two of the above point values.

[0144] In one embodiment, the coverage rate of the coating layer on the surface of the positive electrode active material is 80% to 100%.

[0145] That is, the coating layer can be coated on the surface of the positive electrode active material in the form of full coating or non-full coating. It can be understood that full coating means that the coating layer is continuously arranged on the surface of the positive electrode active material so that the positive electrode active material is not exposed. In this way, during the preparation of the positive electrode slurry, the positive electrode active material will not be exposed from the coating layer and contact with water, thereby improving the water-isolating effect of the coating layer.

[0146] In the above 80% to 100%, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 80%, 85%, 80%, 95%, 100%, etc., as well as the range values ​​between any two of the above point values.

[0147] In one embodiment, the surface of the positive electrode active material includes adsorption groups, and the adsorption groups include at least one of hydroxyl groups, amino groups, and carboxyl groups.

[0148] Some positive electrode active materials have some adsorption groups such as hydroxyl and carboxyl on their surfaces. These adsorption groups on the surface of the positive electrode active materials help the constituent monomers of the organic polymer to be effectively adsorbed on the surface of the positive electrode active material, making it convenient for the constituent monomers of the organic polymer to polymerize on the surface of the positive electrode active material to form a coating layer, which helps the coating layer to be effectively coated on the surface of the positive electrode active material.

[0149] It is understood that the adsorption group includes but is not limited to at least one of a hydroxyl group, an amino group, and a carboxyl group.

[0150] In one embodiment, the positive electrode active material includes at least one of a layered lithium transition metal oxide, an olivine phase lithium-containing phosphate, and a spinel phase lithium-containing manganese-based oxide. Optionally, the positive electrode active material includes at least one of the compounds represented by formula (1), formula (2), and formula (3), Li a1 Ni x1 Co y1 M1 z1 R b1 O c1 Formula (1), wherein 0.6≤a1≤1.2, 0.3≤x1≤1, 0≤y1≤0.4, 0<z1≤0.2, 0<b1≤0.2, 1.8≤c1≤2.2, x1+y1+z1+b1=1, M1 is selected from one or two of Mn and Al, and R includes one or more of Na, Sb, K, Ca, Zr, Sr, Al, B, Ba, Nb, W, Mo, Co, Ti, and Mg; Li x2 A y2 Me a2 M2 b2 P 1-c2 X c2 Y z2 Formula (2), in which 0.5≤x2≤1.3, 0≤y2≤1.3, and 0.9≤x2+y2≤1.3; 0.9≤a2≤1.5, 0≤b2≤0.5, and 0.9≤a2+b2≤1.5; 0≤c2≤0.5; 3≤z2≤5; A includes one or more of Na, K, and Mg; Me includes one or more of Mn, Fe, Co, and Ni; M2 includes one or more of B, Mg, Al, Si, P, S, Ca, Sc, Ti, V, Cr, Cu, Zn, Sr, Y, Zr, Nb, Mo, Cd, Sn, Sb, Te, Ba, Ta, W, Yb, La, and Ce; X includes one or more of S, Si, Cl, B, C, and N; Y includes one or more of O and F; Li 1+z3 Mnc3 Z 2-c3 O 4-d B d Formula (3), in Formula (3), -0.5 ≤ z3 ≤ 0.2, 0 < c3 ≤ 2, 0 ≤ d < 1, Z includes one or more of Ni, Fe, Cr, Ti, Zn, V, Al, Mg, Zr, and Ce, and B includes one or more of S, N, F, Cl, Br, and I.

[0151] It can be understood that the positive electrode active material includes, but is not limited to, at least one of layered lithium transition metal oxides, olivine phase lithium-containing phosphates, and spinel phase lithium-containing manganese-based oxides. Further, the positive electrode active material includes, but is not limited to, at least one of the compounds of Formula (1), Formula (2), and Formula (3) shown. For example, Li a1 Ni x1 Co y1 M1 z1 R b1 O c1 Formula (1), in Formula (1), 0.6 ≤ a1 ≤ 1.2, 0.3 ≤ x1 ≤ 1, 0 ≤ y1 ≤ 0.4, 0 < z1 ≤ 0.2, 0 < b1 ≤ 0.2, 1.8 ≤ c1 ≤ 2.2, x1 + y1 + z1 + b1 = 1, M1 is selected from one or two of Mn and Al, and R includes one or more of Na, Sb, K, Ca, Zr, Sr, Al, B, Ba, Nb, W, Mo, Co, Ti, and Mg; Li x2 A y2 Me a2 M2 b2 P 1-c2 X c2 Y z2 Formula (2), in Formula (2), 0.5 ≤ x2 ≤ 1.3, 0 ≤ y2 ≤ 1.3, and 0.9 ≤ x2 + y2 ≤ 1.3; 0.9 ≤ a2 ≤ 1.5, 0 ≤ b2 ≤ 0.5, and 0.9 ≤ a2 + b2 ≤ 1.5; 0 ≤ c2 ≤ 0.5; 3 ≤ z2 ≤ 5; A includes one or several of Na, K, and Mg; Me includes one or several of Mn, Fe, Co, and Ni; M2 includes one or several of B, Mg, Al, Si, P, S, Ca, Sc, Ti, V, Cr, Cu, Zn, Sr, Y, Zr, Nb, Mo, Cd, Sn, Sb, Te, Ba, Ta, W, Yb, La, and Ce; X includes one or several of S, Si, Cl, B, C, and N; Y includes one or several of O and F; Li 1+z3 Mn c3 Z 2-c3 O 4-d B dFormula (3), in Formula (3), -0.5 ≤ z3 ≤ 0.2, 0 < c3 ≤ 2, 0 ≤ d < 1, Z includes one or more of Ni, Fe, Cr, Ti, Zn, V, Al, Mg, Zr and Ce, and B includes one or more of S, N, F, Cl, Br and I. The positive electrode active material of the present application includes, but is not limited to, substances such as lithium iron phosphate, lithium cobaltate, lithium manganate, lithium iron manganese phosphate, etc. The positive electrode active material contained in the positive electrode sheet is rich in transition metals such as lithium, iron, cobalt, and nickel, and less loss of iron and transition metal elements occurs during the production of the electrode sheet, thereby improving the cycle performance of the battery.

[0152] In one embodiment, the coating layer includes a solid electrolyte and / or a conductive agent; the mass percentage of the solid electrolyte in the total mass of the coating layer is 0.01% to 2%, preferably 0.5% to 1.5%. The solid electrolyte includes at least one of P2O5, B2O3, SiO2, Li2O, Li2S, SiS2, LiPON, LiSiPON, LiSON; the mass percentage of the conductive agent in the total mass of the coating layer is 0.01% to 2%, preferably 0.5% to 1.5%. The conductive agent includes at least one of SP and CNT.

[0153] Including a solid electrolyte in the coating layer can help the migration of lithium ions, and including a conductive agent in the coating layer can improve electron conduction.

[0154] Among the above 0.01% to 2%, the values include the minimum and maximum values of this range, as well as each value between such minimum and maximum values. Specific examples include, but are not limited to, the point values in the embodiments and 0.01%, 0.05%, 0.1%, 0.15%, 0.5%, 0.8%, 1.0%, 1.5%, 2%, etc., as well as the range values between any two of the above point values.

[0155] In one embodiment, the present application also provides a method for preparing a positive electrode material, including: providing a positive electrode active material; mixing the positive electrode active material with the constituent monomers of an organic polymer to obtain a first mixed solution; mixing an initiator, a catalyst and a solvent to obtain a second mixed solution; mixing the first mixed solution with the second mixed solution and heating to obtain a positive electrode material, and the positive electrode material includes a positive electrode active material and a hydrophobic coating layer provided on the surface of the positive electrode active material.

[0156] That is, the coating layer of the organic polymer is formed by polymerizing monomers on the surface of the positive electrode active material. In the step of preparing the positive electrode material, a positive electrode active material is provided, and the positive electrode active material is mixed with the constituent monomers of the organic polymer to obtain a first mixed liquid, so that the constituent monomers of the organic polymer are arranged on the surface of the positive electrode active material to facilitate the polymerization reaction of the constituent monomers of the organic polymer on the surface of the positive electrode active material, thereby forming a coating layer, and an initiator, a catalyst and a solvent are mixed to obtain a second mixed liquid, that is, an initiator and a catalyst for the polymerization reaction of the constituent monomers of the organic polymer are prepared, the first mixed liquid is mixed with the second mixed liquid, so that the constituent monomers of the organic polymer are in contact with the initiator and the catalyst, and the positive electrode material is heated to obtain the positive electrode material, which includes the positive electrode active material and a hydrophobic coating layer arranged on the surface of the positive electrode active material.

[0157] In one embodiment, the step of mixing the positive electrode active material with the constituent monomers of the organic polymer to obtain the first mixed solution includes: mixing the positive electrode active material with the constituent monomers of the organic polymer, a solid electrolyte and / or a conductive agent to obtain the first mixed solution.

[0158] In order to include a solid electrolyte and / or a conductive agent in the coating layer, the solid electrolyte and / or the conductive agent are added during the process of mixing the positive electrode active material with the constituent monomers of the organic polymer, so that the constituent monomers of the organic polymer can mix the solid electrolyte and / or the conductive agent into the coating layer during the polymerization process.

[0159] In one embodiment, the mass ratio of the positive electrode active material, the constituent monomer of the organic polymer, the initiator, and the catalyst is (88%-99.9%): (0.1%-4%): (0%-4%): (0%-4%), preferably, (95.5%-98.5%): (0.5%-1.5%): (0.5%-1.5%): (0.5%-1.5%); and / or, the initiator includes an organic peroxide (such as benzoyl peroxide, methyl ethyl ketone peroxide) The invention relates to a method for preparing an organic polymer comprising: preparing an organic polymer comprising at least one of inorganic peroxides (such as potassium persulfate, ammonium persulfate, etc.), azo compounds (such as azobisisobutyronitrile, etc.), benzyl alcohol, and potassium permanganate; and / or the catalyst comprises at least one of 1,8-diazabicycloundec-7-ene, tetrabutylammonium bromide, and p-toluenesulfonic acid; and / or the solvent comprises at least one of dichloromethane, an aqueous sodium bisphenolate solution, and toluene; and / or the constituent monomers of the organic polymer comprise at least one of olefin carbonates, olefins, and amides.

[0160] In the step of preparing the positive electrode material, the mass ratio of the positive electrode active material, the constituent monomers of the organic polymer, the initiator, and the catalyst is (88%-99.9%): (0.1%-4%): (0%-4%): (0%-4%), preferably, (95.5%-98.5%): (0.5%-1.5%): (0.5%-1.5%): (0.5%-1.5%). As long as the mass ratio of each raw material is within the above range, the positive electrode material can be effectively prepared.

[0161] It is understood that an initiator refers to a substance that can initiate a polymerization reaction of a monomer. For example, a free radical initiator refers to a compound that is easily decomposed into free radicals (i.e., primary free radicals) by heat, and can be used to initiate free radical polymerization and copolymerization reactions of olefinic and diene monomers. Initiators include, but are not limited to, at least one of organic peroxides (such as benzoyl peroxide, methyl ethyl ketone peroxide, etc.), inorganic peroxides (such as potassium persulfate, ammonium persulfate, etc.), azo compounds (such as azobisisobutyronitrile, etc.), benzyl alcohol, and potassium permanganate. Those skilled in the art can select a suitable initiator according to the type of monomers constituting the organic polymer.

[0162] Catalysts are substances that can change the chemical reaction rate of reactants in chemical reactions (either increase or decrease) without changing the chemical equilibrium, and whose quality and chemical properties do not change before and after the chemical reaction. Catalysts include but are not limited to at least one of 1,8-diazabicycloundec-7-ene, tetrabutylammonium bromide, and p-toluenesulfonic acid. Those skilled in the art can select a suitable catalyst according to the needs of the monomer polymerization reaction.

[0163] The solvent in the present application includes but is not limited to at least one of dichloromethane, sodium bisphenolate aqueous solution, and toluene.

[0164] The constituent monomers of the organic polymer in the present application include but are not limited to at least one of alkylene carbonates, olefins, and amides. Those skilled in the art can select appropriate monomers to polymerize the coating layer according to the material of the coating layer.

[0165] In the step of preparing the positive electrode material, the mass ratio of the positive electrode active material, the constituent monomers of the organic polymer, the initiator, and the catalyst is (88%-99.9%): (0.1%-4%): (0%-4%): (0%-4%). ​​In the above (88%-99.9%): (0.1%-4%): (0%-4%): (0%-4%), the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 88%: 4%: 4%: 4%, 95.5%: 1.5%: 1.5%: 1.5%, 98.5%: 0.5%: 0.5%: 0.5%, 99%, 0.3%, 0.4%, 0.3%, etc., as well as the range values ​​between any two of the above point values.

[0166] In one embodiment, the steps of mixing a positive electrode active material with a constituent monomer of an organic polymer to obtain a first mixed liquid, mixing an initiator, a catalyst and a solvent to obtain a second mixed liquid, mixing the first mixed liquid with the second mixed liquid, and heating to obtain a positive electrode material include: mixing the positive electrode active material with a constituent monomer of an organic polymer, olefin carbonate, to obtain a first mixed liquid, adding a benzyl alcohol initiator and a 1,8-diazabicycloundec-7-ene catalyst to dichloromethane, dissolving them to obtain a second mixed liquid, mixing the first mixed liquid with the second mixed liquid, heating to 50° C. to 60° C., and reacting for 6 h to 8 h to obtain a positive electrode material.

[0167] In one embodiment, the present application also provides a positive electrode plate, which includes a current collector and a positive electrode coating provided on at least one side of the current collector, and the positive electrode coating includes the positive electrode material as described above; or, the positive electrode plate includes a current collector and a positive electrode coating provided on at least one side of the current collector, and the positive electrode coating includes the positive electrode material prepared by the method for preparing the positive electrode material as described above.

[0168] In one embodiment, the positive electrode coating includes a dispersant; and / or, the positive electrode coating includes a binder, the binder includes an aqueous binder; and / or, the positive electrode coating includes a conductive agent.

[0169] In order to improve the dispersibility of the positive electrode material and make it evenly distributed in the positive electrode coating, the positive electrode coating includes a dispersant. For example, the dispersant includes but is not limited to polyethyleneimine, polyethylene glycol octylphenyl ether, and the like.

[0170] The positive electrode coating includes a binder, which refers to a material with bonding properties, which is used to bond different substances together. The binder is used to effectively bond the components in the positive electrode coating together. The binder includes an aqueous binder. It can be understood that, in theory, the binder can be oily or aqueous. In an aqueous slurry system, an aqueous binder is used, and in an oily slurry system, an oily binder is used.

[0171] The positive electrode coating includes a conductive agent. The conductive agent is to ensure that the electrode has good charge and discharge performance. A certain amount of conductive material is usually added when the electrode is made. It plays the role of collecting microcurrents between active materials and between active materials and current collectors, so as to reduce the contact resistance of the electrode and accelerate the movement rate of electrons. At the same time, it can also effectively increase the migration rate of lithium ions in the electrode material, thereby improving the charge and discharge efficiency of the electrode.

[0172] In one embodiment, the positive electrode coating includes a dispersant, and the mass of the dispersant accounts for 0.01% to 0.7% of the total mass of the positive electrode coating, preferably, 0.1% to 0.5%; and / or, the positive electrode coating includes an aqueous binder, and the mass of the aqueous binder accounts for 0.1% to 5% of the total mass of the positive electrode coating, preferably, 2% to 4%; and / or, the positive electrode coating includes a conductive agent, and the mass of the conductive agent accounts for 0.1% to 5% of the total mass of the positive electrode coating, preferably, 0.5% to 3%.

[0173] It is understood that the mass of the dispersant accounts for 0.01% to 0.7% of the total mass of the positive electrode coating, preferably 0.1% to 0.5%. The dispersant satisfies the above range and can effectively disperse the components in the positive electrode coating.

[0174] It can be understood that the mass of the aqueous binder accounts for 0.1% to 5% of the total mass of the positive electrode coating, preferably 2% to 4%. The aqueous binder meets the above range so that the components in the positive electrode coating are effectively bonded together.

[0175] It can be understood that the mass of the conductive agent accounts for 0.1% to 5% of the total mass of the positive electrode coating, preferably 0.5% to 3%. The conductive agent meets the above range to improve the charge and discharge efficiency of the battery.

[0176] In the above 0.01% to 0.7%, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, etc., and the range value between any two of the above point values.

[0177] In the above 0.1% to 0.5%, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, etc., and the range values ​​between any two of the above point values.

[0178] In the above-mentioned 0.1% to 5%, the values ​​include the minimum and maximum values ​​of the range, and every value between such minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.8%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, etc., and the range values ​​between any two of the above-mentioned point values.

[0179] In the above 2% to 4%, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 2%, 2.2%, 2.5%, 2.7%, 3%, 3.2%, 3.5%, 3.7%, 4%, etc., and the range values ​​between any two of the above point values.

[0180] In the above-mentioned 0.5% to 3%, the values ​​include the minimum and maximum values ​​of the range, and every value between such minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3%, etc., as well as the range values ​​between any two of the above-mentioned point values.

[0181] In one embodiment, the positive electrode coating includes a dispersant, and the dispersant includes at least one of a cationic dispersant and an amphoteric dispersant; and / or, the positive electrode coating includes an aqueous binder, and the aqueous binder includes at least one of methyl cellulose and its salts, xanthan gum and its salts, chitosan and its salts, alginate and its salts, polyacrylamide, acrylonitrile-acrylic acid copolymer and its derivatives, acrylonitrile-acrylate copolymer, and acrylonitrile-acrylic acid-acrylate copolymer; and / or, the positive electrode coating includes a conductive agent, and the conductive agent includes at least one of carbon black, graphite, graphene, and carbon nanotubes.

[0182] It is understood that the dispersant includes but is not limited to at least one of a cationic dispersant and an amphoteric dispersant.

[0183] The aqueous binder includes, but is not limited to, at least one of methylcellulose and its salts, xanthan gum and its salts, chitosan and its salts, alginic acid and its salts, polyacrylamide, acrylonitrile-acrylic acid copolymer and its derivatives, acrylonitrile-acrylate copolymer, and acrylonitrile-acrylic acid-acrylate copolymer.

[0184] The conductive agent includes but is not limited to at least one of carbon black, graphite, graphene, and carbon nanotubes.

[0185] In one embodiment, the positive electrode coating includes at least one of a cationic dispersant and an amphoteric dispersant, the cationic dispersant includes at least one of an amine salt, a quaternary ammonium salt, and a pyridinium salt, and the amphoteric dispersant includes at least one of a phosphate salt and a polyacrylamide; and / or, the positive electrode coating includes a binder, the binder includes an acrylonitrile-acrylic acid-acrylate copolymer, preferably, the number average molecular weight of the acrylonitrile-acrylic acid-acrylate copolymer is 300,000 to 2,000,000.

[0186] The cationic dispersant includes but is not limited to at least one of amine salts, quaternary ammonium salts, and pyridinium salts, and the amphoteric dispersant includes but is not limited to at least one of phosphate salts and polyacrylamide.

[0187] It can be understood that cationic dispersants: interact with negatively charged surfaces and disperse particles well in water through electrostatic adsorption; amphoteric dispersants: form a bimolecular structure on the surface of the material. Amphoteric dispersants have a strong affinity for water, which increases the degree of wetting of solid particles by water. The solid particles move away from each other due to electrostatic repulsion to achieve a good dispersion effect.

[0188] Dispersants can be divided into cationic dispersants, amphoteric dispersants, anionic dispersants, nonionic dispersants, etc. according to the different electrical properties of the ions they generate in water. Cationic dispersants refer to compounds that generate positive charges in water, while amphoteric dispersants refer to compounds that generate positive and negative charges in water.

[0189] The acrylonitrile-acrylic acid-acrylate copolymer has good adhesion and flexibility, and using it as a binder can improve the adhesion between the positive electrode coating and the current collector. The number average molecular weight of the acrylonitrile-acrylic acid-acrylate copolymer is within the above range, so that the acrylonitrile-acrylic acid-acrylate copolymer has good adhesion and suitable viscosity.

[0190] In one embodiment, the present application further provides a positive electrode slurry, the positive electrode slurry includes the positive electrode material as described above; or, the positive electrode slurry includes the positive electrode material prepared by the preparation method of the positive electrode material as described above.

[0191] In one embodiment, the positive electrode slurry includes a dispersant, the mass of the dispersant accounts for 0.01% to 0.7% of the total mass of the solid matter in the positive electrode slurry, preferably, 0.1% to 0.5%, and the dispersant includes at least one of a cationic dispersant and an amphoteric dispersant; and / or, the positive electrode slurry includes an aqueous binder, the mass of the aqueous binder accounts for 0.1% to 5% of the total mass of the solid matter in the positive electrode slurry, preferably, 2% to 4%, and the aqueous binder includes at least one of methyl cellulose and its salts, xanthan gum and its salts, chitosan and its salts, alginic acid and its salts, polyacrylamide, acrylonitrile-acrylic acid copolymer and its derivatives, acrylonitrile-acrylate copolymer, and acrylonitrile-acrylic acid-acrylate copolymer; and / or, the positive electrode slurry includes a conductive agent, the mass of the conductive agent accounts for 0.1% to 5% of the total mass of the solid matter in the positive electrode slurry, preferably, 0.5% to 3%, and the conductive agent includes at least one of carbon black, graphite, graphene, and carbon nanotubes.

[0192] In one embodiment, the positive electrode slurry includes a solvent, the solvent includes water; and / or the solid content of the positive electrode slurry is 40% to 90%, preferably, 50% to 70%; and / or the viscosity of the positive electrode slurry is 100cp to 10000cp, preferably, 3000cp to 7000cp.

[0193] The positive electrode slurry of the present application can be an aqueous positive electrode slurry, that is, the solvent includes water. In an aqueous environment, the positive electrode material of the present application has good stability. A coating layer is arranged on the surface of the positive electrode active material, so that during the preparation process of the aqueous positive electrode slurry, the coating layer blocks the contact between water and the positive electrode active material, thereby reducing the problem of metal ion precipitation in the positive electrode active material, thereby improving the cycle performance of the battery.

[0194] The solid content of the positive electrode slurry is within the above range, which can improve the processing performance of the slurry and reduce the problem of cracking of the electrode piece. The viscosity of the positive electrode slurry is within the above range, which facilitates the processing of the slurry.

[0195] In the above-mentioned 40% to 90%, the values ​​include the minimum and maximum values ​​of the range, and every value between such minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 40%, 42%, 45%, 48%, 50%, 52%, 55%, 58%, 60%, 62%, 65%, 68%, 70%, 72%, 75%, 78%, 80%, 82%, 85%, 88%, 90%, etc., and the range values ​​between any two of the above-mentioned point values.

[0196] In the above 50% to 70%, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 50%, 52%, 55%, 58%, 60%, 62%, 65%, 68%, 70%, etc., as well as the range values ​​between any two of the above point values.

[0197] In the above-mentioned 100cp to 10000cp, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 100cp, 200cp, 500cp, 800cp, 1000cp, 1000cp, 1200cp, 1500cp, 1800cp, 2000cp, 3000cp, 4000cp, 5000cp, 6000cp, 7000cp, 8000cp, 9000cp, 10000cp, etc., and the range value between any two of the above-mentioned point values.

[0198] In the above-mentioned 3000cp to 7000cp, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 3000cp, 3500cp, 4000cp, 4500cp, 5000cp, 5500cp, 6000cp, 6500cp, 7000cp, etc., as well as the range values ​​between any two of the above-mentioned point values.

[0199] In one embodiment, the present application also provides a method for preparing the positive electrode slurry as described above, comprising: mixing the positive electrode material and the dispersant to form a mixture; and mixing the mixture, the conductive agent, the aqueous binder and the solvent water to obtain the positive electrode slurry.

[0200] The present application also provides a battery, which includes the positive electrode plate as described above.

[0201] The present application also provides an electrical device, which includes the battery as described above.

[0202] In addition, the battery (secondary battery, battery module, battery pack) and the electric device of the present application will be described below with reference to the drawings as appropriate.

[0203] In one embodiment of the present application, a secondary battery is provided.

[0204] Typically, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charge and discharge process, active ions are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through. The separator is the separator improved above in this application.

[0205] The positive electrode plate includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector.

[0206] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.

[0207] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0208] The battery will be accompanied by Li deintercalation and consumption during the charge and discharge process, and the molar content of Li is different when the battery is discharged to different states. In the list of positive electrode materials in this application, the molar content of Li is the initial state of the material, that is, the state before feeding. The positive electrode material is used in the battery system, and the molar content of Li will change after charge and discharge cycles.

[0209] In the list of positive electrode materials in this application, the molar content of O is only a theoretical value. The release of oxygen from the lattice will cause the molar content of oxygen to change, and the actual molar content of O will fluctuate.

[0210] In some embodiments, the positive electrode film layer may also optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0211] In some embodiments, the positive electrode film layer may further include a conductive agent, for example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0212] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0213] The negative electrode plate includes a negative electrode current collector and a negative electrode film layer arranged on at least one surface of the negative electrode current collector, and the negative electrode film layer includes a negative electrode active material.

[0214] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0215] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0216] In some embodiments, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0217] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).

[0218] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0219] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0220] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0221] The electrolyte plays a role in conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs.

[0222] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.

[0223] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0224] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.

[0225] In some embodiments, the battery cell may include an outer packaging, which may be used to encapsulate the electrode assembly and the electrolyte.

[0226] In some embodiments, the outer packaging of the battery cell may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the battery cell may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0227] The present application has no particular limitation on the shape of the battery cell, which may be cylindrical, square or any other shape. Figure 2 The battery cell 5 is a square structure as an example.

[0228] In some embodiments, reference Figure 3, the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the diaphragm can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, and those skilled in the art can select according to specific actual needs.

[0229] In some embodiments, a battery cell pool may be assembled into a battery module. The number of battery cells contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.

[0230] Figure 4 4 is an example of a battery module. Figure 4 In the battery module 4, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 5 may be fixed by fasteners.

[0231] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of battery cells 5 are received in the receiving space.

[0232] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.

[0233] Figure 5 and Figure 6 1 is a battery pack 1 as an example. Figure 5 and Figure 6 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.

[0234] In addition, the present application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0235] As an electrical device, a battery cell, a battery module or a battery pack can be selected according to its usage requirements.

[0236] Figure 7 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the power consumption device's requirements for high power and high energy density of battery cells, a battery pack or a battery module can be used.

[0237] As another example, the device may be a mobile phone, a tablet computer, a notebook computer, etc. The device is usually required to be light and thin, and a battery cell may be used as a power source.

[0238] Example

[0239] Example 1

[0240] Preparation of cathode materials

[0241] (1) Add 10 g of ethylene carbonate to lithium iron phosphate powder with a Dv50 of 1.06 μm, stir and mix well to obtain a suspension for later use;

[0242] (2) 10 g of benzyl alcohol initiator and 20 g of 1,8-diazabicycloundec-7-ene (DBU) catalyst were added to 100 g of dichloromethane, slowly stirred until completely dissolved, and then mixed with the suspension obtained in step (1), the system was sealed and heated to 55° C. in a water bath, and 350 g of n-hexane was added after reacting for 6 h. After standing for 20 min, the precipitate was separated by filtration, and dried in a vacuum oven at 120° C. to obtain a lithium iron phosphate positive electrode material (the coating layer was fully coated on the surface of the positive electrode active material). Through the preparation of the positive electrode material, the mass percentage of the coating layer to the mass percentage of the entire positive electrode material was 10 g / (10 g+1000 g)×100%=0.99%.

[0243] Preparation of positive electrode

[0244] First, the positive electrode material, conductive agent (conductive carbon black SP), and dispersant (polyethyleneimine) prepared according to the above steps are uniformly mixed in a weight ratio of 98.7:1:0.3; then, the mixture of the positive electrode material, conductive agent (conductive carbon black SP), dispersant (polyethyleneimine) prepared according to the above steps and aqueous binder (acrylonitrile-acrylate copolymer) are mixed in a weight ratio of 98:2, and LA-133 is used as the aqueous binder; deionized water is used as a solvent to stir and mix uniformly to obtain a positive electrode slurry with a solid content of 50%; then the positive electrode slurry is uniformly coated on the positive electrode collector, and then dried, cold pressed, and cut to obtain a positive electrode sheet.

[0245] Preparation of negative electrode

[0246] The active material artificial graphite, the conductive agent (conductive carbon black SP), the binder styrene-butadiene rubber (SBR), and the thickener sodium hydroxymethyl cellulose (CMC) are dissolved in the solvent deionized water in a weight ratio of 96.2:0.8:0.8:1.2, and the negative electrode slurry is prepared after being evenly mixed; the negative electrode slurry is evenly coated on the negative electrode collector copper foil once or multiple times, and the negative electrode sheet is obtained after drying, cold pressing, and slitting.

[0247] Preparation of electrolyte

[0248] In an argon atmosphere glove box (H2O<0.1ppm, O2<0.1ppm), the organic solvents ethylene carbonate (EC) / ethyl methyl carbonate (EMC) were mixed in a volume ratio of 3 / 7, 12.5% ​​LiPF6 lithium salt was added and dissolved in the organic solvent, and stirred evenly to obtain the electrolyte of Example 1.

[0249] Diaphragm

[0250] A polypropylene membrane was used as the separator.

[0251] Preparation of batteries

[0252] The positive electrode sheet, separator, and negative electrode sheet of Example 1 are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare cell, and the bare cell is welded with a pole ear, and the bare cell is placed in an aluminum shell, and baked at 80°C to remove water, and then the electrolyte is injected and sealed to obtain an uncharged battery. The uncharged battery is then subjected to the processes of static, hot and cold pressing, formation, shaping, and capacity testing in sequence to obtain the lithium ion battery product of Example 1.

[0253] Example 2 to Example 5

[0254] On the basis of Example 1, the percentage of the mass of the coating layer to the mass of the positive electrode material is adjusted.

[0255] Example 6 and Example 7

[0256] Based on Example 1, the types of positive electrode active materials were adjusted, wherein the Dv50 of NCM523 was 1.06 μm, and the LiFe 0.4 Mn 0.6 The Dv50 of PO4 is 0.7μm.

[0257] Example 8 and Example 9

[0258] On the basis of Example 1, the material type of the coating layer was adjusted.

[0259] Example 10

[0260] On the basis of Example 1, a solid electrolyte is included in the coating layer. In the process of preparing the coating layer, the steps of adding the solid electrolyte are as follows: (1) adding lithium iron phosphate powder to 10g of ethylene carbonate and P2O5, stirring and mixing evenly to obtain a suspension for use.

[0261] Embodiment 11

[0262] On the basis of Example 1, a solid electrolyte and a conductive agent are included in the coating layer, wherein in the preparation step of the positive electrode material, the step of adding the solid electrolyte and the conductive agent is as follows: (1) add lithium iron phosphate powder to 10g of ethylene carbonate, P2O5, and SP, stir and mix evenly, and obtain a suspension for use.

[0263] Comparative Example 1

[0264] On the basis of Example 1, the positive electrode active material was not coated with the coating layer.

[0265] Comparative Example 2

[0266] On the basis of Example 6, the positive electrode active material was not coated with the coating layer.

[0267] Comparative Example 3

[0268] On the basis of Example 7, the positive electrode active material was not coated with the coating layer.

[0269] Performance testing steps

[0270] Positive electrode cohesion test

[0271] That is, 180° shear strength test. Take the positive electrode to be tested, select the positive electrode with good appearance, and do not allow the appearance of bad products. Use a blade to cut a sample with a width of 30mm and a length of 160mm. Stick the special double-sided tape NITTO NO.5000NS on the steel plate, with a tape width of 20mm and a length of 140mm. Stick the fixed-size electrode sample cut above on the double-sided tape, with the test surface facing up, and then stick the low-viscosity green tape four-dimensional MY2G test tape with a width of 20mm and a length greater than the sample length of 80-200mm flat on the test surface, and then use a 3kg pressure roller to roll it three times in the same direction along the surface of the positive electrode. Then fix the sample on the testing machine, fix the end of the steel plate without the electrode with the lower clamp, fold the green glue upwards and fix it with the upper clamp, keep the axis direction of the electrode consistent with the direction of force, load the testing machine at a peeling speed of 10mm / min, stop the test when the stress indication of the testing machine is stable, record the maximum load force as F (unit N), the electrode width L = 20mm, and calculate the shear strength f (unit N / m) based on f = F / L.

[0272] Battery performance test

[0273] Initial gram capacity test of positive electrode material

[0274] Taking Example 1 as an example, the positive electrode material is lithium iron phosphate, and the initial gram capacity test process of the positive electrode material is as follows: at 25°C, the battery corresponding to Example 1 is charged to 3.65V at a constant current of 1 / 3C, then charged to a current of 0.05C at a constant voltage of 3.65V, left for 5 minutes, and then discharged to 2.5V at 1 / 3C. The obtained capacity is divided by the mass of the positive electrode material in the positive electrode to obtain the initial gram capacity of the positive electrode material.

[0275] For Example 6 and Comparative Example 2, the positive electrode material is NCM523, and the charge and discharge currents during the initial gram capacity test of the positive electrode material are the same as above. The upper limit cutoff voltage of the charge is 4.2V, and the lower limit cutoff voltage is 2.8V.

[0276] For Example 7 and Comparative Example 1, the positive electrode material is LiFe 0.4 Mn 0.6 PO4, the charge and discharge currents during the initial gram capacity test of the positive electrode material are the same as above, the upper limit cut-off voltage of the charge is 4.3V, and the lower limit cut-off voltage is 2.5V.

[0277] Table 1

[0278]

[0279] It can be seen from the above table that, by comparing the embodiments with the comparative examples, a coating layer is provided on the surface of the positive electrode active material. During the preparation of the aqueous positive electrode slurry, the coating layer can prevent water from contacting the positive electrode active material, thereby reducing the loss of metal ions in the positive electrode active material, effectively improving the gram capacity of the positive electrode material, and improving the cohesive force of the positive electrode sheet, which helps to improve the manufacturing pollution of the battery, reduce the manufacturing cost, and ensure that the battery still has good cycle performance.

[0280] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. All equivalent structural changes made using the contents of the present invention's specification and drawings, or directly / indirectly applied in other related technical fields, are included in the patent protection scope of the present invention.

Claims

1. A positive electrode material, characterized in that: The invention comprises a positive electrode active material and a coating layer arranged on the surface of the positive electrode active material, wherein the coating layer comprises an organic polymer, and preferably, the coating layer comprises a hydrophobic organic polymer.

2. The positive electrode material according to claim 1, characterized in that The hydrophobic organic polymer includes at least one of polycarbonate, polyolefin, polyamide and polyacrylonitrile.

3. The positive electrode material according to claim 1 or 2, characterized in that The coating layer also includes a solid electrolyte and / or a conductive agent; Optionally, the mass of the solid electrolyte accounts for 0.01% to 2% of the total mass of the coating layer, preferably 0.5% to 1.5%; The solid electrolyte includes at least one of P2O5, B2O3, SiO2, Li2O, Li2S, SiS2, LiPON, LiSiPON, and LiSON; The mass of the conductive agent accounts for 0.01% to 2% of the total mass of the coating layer, preferably 0.5% to 1.5%; The conductive agent includes at least one of SP and CNT.

4. The positive electrode material according to any one of claims 1 to 3, characterized in that The mass of the coating layer accounts for 0.01% to 2% of the total mass of the positive electrode material, preferably 0.1% to 1.5%.

5. The positive electrode material according to any one of claims 1 to 4, characterized in that The thickness of the coating layer ranges from 1 nm to 200 nm, preferably, from 10 nm to 50 nm.

6. The positive electrode material according to any one of claims 1 to 5, characterized in that The coating layer has a coverage rate of 80% to 100% on the surface of the positive electrode active material.

7. The positive electrode material according to any one of claims 1 to 6, characterized in that The surface of the positive electrode active material includes adsorption groups, and the adsorption groups include at least one of hydroxyl groups, amino groups, and carboxyl groups.

8. The positive electrode material according to any one of claims 1 to 7, characterized in that The positive electrode active material comprises at least one of a layered lithium transition metal oxide, an olivine phase lithium-containing phosphate, and a spinel phase lithium-containing manganese-based oxide. Optionally, the positive electrode active material includes at least one of the compounds represented by formula (1), formula (2) and formula (3), Li a1 Ni x1 Co y1 M1 z1 R b1 O c1 Formula (1) In the formula (1), 0.6≤a1≤1.2, 0.3≤x1≤1, 0≤y1≤0.4, 0<z1≤0.2, 0<b1≤0.2, 1.8≤c1≤2.2, x1+y1+z1+b1=1, M1 is selected from one or two of Mn and Al, and R includes one or more of Na, Sb, K, Ca, Zr, Sr, Al, B, Ba, Nb, W, Mo, Co, Ti, and Mg; Li x2 A y2 Me a2 M2 b2 P 1-c2 X c2 Y z2 Formula (2) In the formula (2), 0.5≤x2≤1.3, 0≤y2≤1.3, and 0.9≤x2+y2≤1.3; 0.9≤a2≤1.5, 0≤b2≤0.5, and 0.9≤a2+b2≤1.5; 0≤c2≤0.5; 3≤z2≤5; A includes one or more of Na, K, and Mg; Me includes one or more of Mn, Fe, Co, and Ni; M2 includes one or more of B, Mg, Al, Si, P, S, Ca, Sc, Ti, V, Cr, Cu, Zn, Sr, Y, Zr, Nb, Mo, Cd, Sn, Sb, Te, Ba, Ta, W, Yb, La, and Ce; X includes one or more of S, Si, Cl, B, C, and N; Y includes one or more of O and F; Li 1+z3 Mn c3 Z 2-c3 O 4-d B d Formula (3) In the formula (3), -0.5 ≤ z3 ≤ 0.2, 0 < c3 ≤ 2, 0 ≤ d < 1, Z includes one or more of Ni, Fe, Cr, Ti, Zn, V, Al, Mg, Zr and Ce, and B includes one or more of S, N, F, Cl, Br and I.

9. A method for preparing the positive electrode material according to any one of claims 1 to 8, characterized in that: Comprising: Providing a positive electrode active material; Mixing the positive electrode active material with a monomer constituting an organic polymer to obtain a first mixed solution; Mixing an initiator, a catalyst and a solvent to obtain a second mixed solution; Mixing the first mixed solution with the second mixed solution and heating to obtain the positive electrode material, the positive electrode material comprising the positive electrode active material and a coating layer provided on the surface of the positive electrode active material, the coating layer comprising the organic polymer, preferably, the coating layer comprises a hydrophobic organic polymer.

10. The method for preparing the positive electrode material according to claim 9, characterized in that: In the step of mixing the positive electrode active material with a monomer constituting an organic polymer to obtain a first mixed solution, it includes: Mixing the positive electrode active material with a monomer constituting an organic polymer, a solid electrolyte and / or a conductive agent to obtain a first mixed solution.

11. The method for preparing a positive electrode material according to claim 9 or 10, characterized in that: The mass ratio of the positive electrode active material, the monomer constituting the organic polymer, the initiator, and the catalyst is (88% - 99.9%):(0.1% - 4%):(0% - 4%):(0% - 4%), preferably, (95.5% - 98.5%):(0.5% - 1.5%):(0.5% - 1.5%):(0.5% - 1.5%); And / or, the initiator includes at least one of organic peroxides, inorganic peroxides, azo compounds, benzyl alcohol, potassium permanganate, the organic peroxides include at least one of benzoyl peroxide, methyl ethyl ketone peroxide, the inorganic peroxides include at least one of potassium persulfate, ammonium persulfate, and the azo compounds include azobisisobutyronitrile; And / or, the catalyst includes at least one of 1,8-diazabicycloundec-7-ene, tetrabutylammonium bromide, p-toluenesulfonic acid; And / or, the solvent includes at least one of dichloromethane, sodium bisphenolate aqueous solution, toluene; And / or, the monomer constituting the organic polymer includes at least one of carbonic acid esters, olefins, amides.

12. The method for preparing a positive electrode material according to any one of claims 9 to 11, characterized in that: In the step of mixing the positive electrode active material with a monomer constituting an organic polymer to obtain a first mixed solution, mixing an initiator, a catalyst and a solvent to obtain a second mixed solution, mixing the first mixed solution with the second mixed solution and heating to obtain a positive electrode material, it includes: Mixing the positive electrode active material with a carbonic acid ester monomer constituting an organic polymer to obtain a first mixed solution, adding a benzyl alcohol initiator and a 1,8-diazabicycloundec-7-ene catalyst to dichloromethane and dissolving to obtain a second mixed solution, mixing the first mixed solution with the second mixed solution, heating to 50°C to 60°C, and reacting for 6h to 8h to obtain a positive electrode material.

13. A positive electrode plate, characterized in that: The positive electrode plate includes a current collector and a positive electrode coating provided on at least one side of the current collector, and the positive electrode coating includes the positive electrode material according to any one of claims 1 to 8; Alternatively, the positive electrode plate comprises a current collector and a positive electrode coating disposed on at least one side of the current collector, and the positive electrode coating comprises a positive electrode material prepared by the method for preparing a positive electrode material as described in any one of claims 9 to 12.

14. The positive electrode sheet according to claim 13, characterized in that: The positive electrode coating includes a dispersant; And / or, the positive electrode coating comprises a binder, and the binder comprises an aqueous binder; And / or, the positive electrode coating includes a conductive agent.

15. The positive electrode sheet according to claim 13 or 14, characterized in that: The positive electrode coating includes a dispersant, and the mass of the dispersant accounts for 0.01% to 0.7% of the total mass of the positive electrode coating, preferably, 0.1% to 0.5%; And / or, the positive electrode coating comprises an aqueous binder, and the mass of the aqueous binder accounts for 0.1% to 5% of the total mass of the positive electrode coating, preferably, 2% to 4%; And / or, the positive electrode coating includes a conductive agent, and the mass of the conductive agent accounts for 0.1% to 5% of the total mass of the positive electrode coating, preferably, 0.5% to 3%.

16. The positive electrode sheet according to any one of claims 13 to 15, characterized in that: The positive electrode coating includes a dispersant, and the dispersant includes at least one of a cationic dispersant and an amphoteric dispersant; And / or, the positive electrode coating comprises an aqueous binder, and the aqueous binder comprises at least one of methyl cellulose and its salts, xanthan gum and its salts, chitosan and its salts, alginic acid and its salts, polyacrylamide, acrylonitrile-acrylic acid copolymer and its derivatives, acrylonitrile-acrylate copolymer, and acrylonitrile-acrylic acid-acrylate copolymer; And / or, the positive electrode coating includes a conductive agent, and the conductive agent includes at least one of carbon black, graphite, graphene, and carbon nanotubes.

17. The positive electrode sheet according to any one of claims 13 to 16, characterized in that: The positive electrode coating includes at least one of a cationic dispersant and an amphoteric dispersant, wherein the cationic dispersant includes at least one of octadecylamine acetate, alkyl quaternary ammonium salt, aminopropylamine dioleate, and quaternary ammonium salt, and the amphoteric dispersant includes at least one of N,N-dimethylaminopropylamine, polyethylene polyamine, octadecylaminopropylamine, ethylene oxide and propylene oxide copolymer, hydroxyl-terminated polyacrylate, and carboxyl-terminated polyacrylate; And / or, the positive electrode coating comprises a binder, the binder comprises acrylonitrile-acrylic acid-acrylate copolymer, preferably, the acrylonitrile-acrylic acid-acrylate copolymer has a number average molecular weight of 300,000 to 2,000,000.

18. A positive electrode slurry, characterized in that: The positive electrode slurry comprises the positive electrode material according to any one of claims 1 to 8; Alternatively, the positive electrode slurry includes a positive electrode material prepared by the method for preparing a positive electrode material according to any one of claims 9 to 12.

19. The positive electrode slurry according to claim 18, characterized in that The positive electrode slurry includes a dispersant, the mass of the dispersant accounts for 0.01% to 0.7% of the total mass of the solid matter in the positive electrode slurry, preferably 0.1% to 0.5%, and the dispersant includes at least one of a cationic dispersant and an amphoteric dispersant; And / or, the positive electrode slurry includes an aqueous binder, the mass of the aqueous binder accounts for 0.1% to 5% of the total mass of solid matter in the positive electrode slurry, preferably 2% to 4%, and the aqueous binder includes at least one of methyl cellulose and its salts, xanthan gum and its salts, chitosan and its salts, alginic acid and its salts, polyacrylamide, acrylonitrile-acrylic acid copolymer and its derivatives, acrylonitrile-acrylate copolymer, and acrylonitrile-acrylic acid-acrylate copolymer; And / or, the positive electrode slurry includes a conductive agent, the mass of the conductive agent accounts for 0.1% to 5% of the total mass of solid matter in the positive electrode slurry, preferably 0.5% to 3%, and the conductive agent includes at least one of carbon black, graphite, graphene, and carbon nanotubes.

20. The positive electrode slurry according to claim 18 or 19, characterized in that: The positive electrode slurry includes a solvent, and the solvent includes water; And / or, the solid content of the positive electrode slurry is 40% to 90%, preferably, 50% to 70%; And / or, the viscosity of the positive electrode slurry is 100 cp to 10000 cp, preferably, 3000 cp to 7000 cp.

21. A method for preparing a positive electrode slurry according to any one of claims 18 to 20, characterized in that: include: Mixing a positive electrode material and a conductive agent to form a mixture; The mixture, the dispersant, the aqueous binder and the solvent water are mixed to obtain a positive electrode slurry.

22. A battery, characterized in that: The battery comprises the positive electrode sheet according to any one of claims 13 to 17.

23. An electrical device, characterized in that: The electrical device comprises the battery as claimed in claim 22.